2009
DOI: 10.1634/theoncologist.2009-s1-1
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Twenty Years of Anemia Management with Erythropoiesis-Stimulating Agents in Nephrology and Oncology/Hematology

Abstract: This article reviews the manuscripts in this issue and summarizes the conclusion that erythropoiesis-stimulating agents are safe and effective in alleviating anemia, diminishing transfusion use, and improving quality of life in symptomatic anemic patients when used according to current guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In this meta-analysis, it was also demonstrated that the use of ESAs is associated with an increased risk of venous thromboembolism (odds ratio = 1.4) [26]. Regarding the increase in the risk for thromboembolic events [23, 27], it must be taken into account specially in patients with cardiovascular disease, in whom the ESA dose must be adjusted according to patient characteristics to avoid an excessive change in plasma volume and maintaining a consistent Hb level [28]. …”
Section: Discussionmentioning
confidence: 99%
“…In this meta-analysis, it was also demonstrated that the use of ESAs is associated with an increased risk of venous thromboembolism (odds ratio = 1.4) [26]. Regarding the increase in the risk for thromboembolic events [23, 27], it must be taken into account specially in patients with cardiovascular disease, in whom the ESA dose must be adjusted according to patient characteristics to avoid an excessive change in plasma volume and maintaining a consistent Hb level [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Epoetin-α, epoetin-β, and darbepoetin-α, modified recombinant EPOs, are also available for clinical use. 75 These agents show similar effectiveness in clinical studies but have some pharmacokinetic differences. Darbepoetin-α boasts a longer half-life, which allows it to be administered every 2 or 3 weeks, although the time to achieve desired hemoglobin values may be longer than those for epoetin; agents with a shorter half-life require weekly administration.…”
Section: Therapeutic Approaches For Anemia In Patients With Cancermentioning
confidence: 99%
“…ESAs, in addition to transfusions and iron therapy, are also usually used in clinical practice to improve anemia in patients with solid tumors and hematological malignancies receiving chemotherapy . ESAs have been approved for the treatment of chemotherapy‐induced anemia since 1993 . These drugs have been demonstrated to ameliorate hemoglobin levels and anemia‐related symptoms and to reduce the need for red blood cell transfusions.…”
Section: Recombinant Human Erythropoietin: Pharmaceutical Formulationmentioning
confidence: 99%